Persepsi Guru Terhadap Sistem Penilaian Prestasi - Hashim, Mohd Zin (1998)

(untitled)
The purpose of this study is to investigate the factors related to perception towards performance appraisal system among national secondary schools teachers in Kuala Terengganu district of Terengganu. The general objective of this study was to measure the teachers’ perception level towards performance appraisal based on evaluation characteristics. Meanwhile the specific objectives were to identify (a) the differences of teachers’ perception level towards performance appraisal system based on demographic factors, i.e. gender, age, teaching experience, length of service, category, rank and salary increment; (b) the influence of independent variables, i.e. demographic factors and evaluation characteristics on teachers’ perception towards performance appraisal system; and (c) the correlation between salary increment factor with evaluation characteristics and teachers’ perception towards performance appraisal system. The respondents of this study were 341 teachers from 12 national secondary schools. The respondents were selected by systematic sampling technique. A set of questionnaire containing demographic data and 43 items using five-points Likert-type scale was applied to measure the teachers’ responses. Three main hypotheses and 12 specific hypotheses were constructed for this study. Statistics tools such as t-test, analysis of variance (ANOVA), multiple regression analysis and Pearson correlation from SPSS software were used to test the hypotheses. The findings revealed that a small majority of teachers have positive perception towards performance appraisal system based on criterion and satisfaction. Specifically the findings indicate that (a) there was significantly different among teachers’ perception towards performance appraisal system based on gender, length of service at the currect school and salary increment; (b) independent variables, i.e.demographic factors dan evaluation characteristics showed significant influences on teachers’ perception towards performance appraisal system; and (c) there was negative and significant correlation between salary increment factor and evaluation characteristics. Some suggestions have been offered based on these findings, to enhance teachers’ perception level towards performance appraisal system.